Peat Soil Temperature Monitoring System With IoT Technology - Hatta Zulkifli; Agus Urip Ari Wibowo; Memen Akbar (International ABEC, 2022)
Peat soil is a soil element that is very susceptible to burning if it is dry and when burned peat will be synonymous with giving rise to dense smoke and giving rise to embers. Prevention has been carried out so far by building a monitoring tower to see the condition of a peatland from a certain height, but because this is done by humans, there will certainly be limitations in monitoring quickly and precisely. By utilizing the development of Internet of Things technology, a solution that can be done by building a system called Silahan Gambut (SILAGA), where this system has been tested on peatlands using the DB18S20 sensor calibrated with a DHT 22 sensor Using Internet of Things technology, it has been successfully monitored in real time the condition of a peatland that has the potential to burn. The results of the sensor data are managed using MongoDB noSQL so that the data obtained is well managed on peat soils at a certain time, condition and region.